HUBUNGAN TINGKAT PENGETAHUAN IBU TENTANG IMUNISASI POLIO DENGAN WAKTU PEMBERIAN IMUNISASI POLIO DI WILAYAH KERJA PUSKESMAS KEDAWUNG KECAMATAN KEDAWUNG KABUPATEN CIREBON - Sofiyati Sofiyati (Pusat Riset dan Inovasi Nasional, 2022)
Polio is a highly contagious and incurable viral infection. The virus attacks the entire body (including muscles and nerves) and can cause permanent muscle weakness and paralysis of one leg. According to the World Health Organization (WHO), polio has paralyzed around a thousand children every day in almost every country in the world. It is important for parents to know why, when, where, and how often their children should be immunized, including polio immunization. Giving immunizations to infants and children not only provides disease prevention to these children but also has a wider impact because it can prevent disease transmission to other children, therefore the knowledge and attitudes of parents, especially mothers, are very important to understand the benefits of immunization for Indonesian children. . Polio immunization is the act of giving polio vaccine (in oral form) or known as the oral polio vaccine (OPV) which aims to provide immunity from poliomyelitis disease. This polio immunization is expected to reduce the number of polio cases in Indonesia, so that people need to be provided with information so that their knowledge about polio immunization can be implemented, especially for mothers who have children under five. This study aims to determine the relationship between the level of knowledge of mothers who have children under five about polio immunization with the time of giving polio immunization at the Kedawung Health Center, Kedawung District, Cirebon Regency. The level of knowledge of mothers who have children under five about polio immunization at the Kedawung Health Center was 44 respondents who were studied, the most respondents were respondents who had sufficient knowledge level. The results of this study prove that there is a relationship between the level of knowledge of mothers who have children under five about polio immunization with the time of giving polio immunization. The Puskesmas should further increase public understanding about polio immunization by providing education in the form of counseling or with other information media so that the information can be reached and accepted by the community so that no more children under five are not immunized against polio.